2008
DOI: 10.1093/annonc/mdm537
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a false-positive MRI on the choice for mastectomy in BRCA mutation carriers is limited

Abstract: Although the rate of false-positive MRI results is high, the impact on the choice for prophylactic mastectomy is limited and is determined by the woman's preference before the establishment of a BRCA mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 24 publications
2
17
0
2
Order By: Relevance
“…Van djik et al [27] found that before testing for genetic BRCA mutations, 25 of 77 women carrying the mutation intended to perform PM and, after a period of 9 months, 19 women had undergone the intervention. Hoogerburg et al [28] found that among the women who intended to undergo PM before genetic results, between 66% and 89% (the variation is dependent on the coexistence of false positive results in MRI surveillance) performed PM at an average period of 2 years post-testing, while only 11% to 15% of women who initially had intentions to adopt the strategy of surveillance for risk reduction, conducted PM. In a study by Kurian et al [29], the majority of patients (85% (CI 68.9% -95.1%)) maintained their attitude against adopting PM interventions or were even more decided not to undergo this intervention, one year after the genetic tests.…”
Section: Choosing Prophylactic Mastectomy (Pm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Van djik et al [27] found that before testing for genetic BRCA mutations, 25 of 77 women carrying the mutation intended to perform PM and, after a period of 9 months, 19 women had undergone the intervention. Hoogerburg et al [28] found that among the women who intended to undergo PM before genetic results, between 66% and 89% (the variation is dependent on the coexistence of false positive results in MRI surveillance) performed PM at an average period of 2 years post-testing, while only 11% to 15% of women who initially had intentions to adopt the strategy of surveillance for risk reduction, conducted PM. In a study by Kurian et al [29], the majority of patients (85% (CI 68.9% -95.1%)) maintained their attitude against adopting PM interventions or were even more decided not to undergo this intervention, one year after the genetic tests.…”
Section: Choosing Prophylactic Mastectomy (Pm)mentioning
confidence: 99%
“…The average age of women who undergo mastectomy interventions was quite variable in the analysed studies; the age range was between 37 and 46 years of age, the majority had children and were married [18][19][20][21][22][23][24][25][26][27][28][29][30]. Women with a history of prior breast cancer are more likely to do prophylactic surgery instead of surveillance (p = 0.003) [20].…”
Section: Choosing Prophylactic Mastectomy (Pm)mentioning
confidence: 99%
See 1 more Smart Citation
“…A major problem with breast MRI is the high incidence of a false positive test result. 8 It is emphasised again that these diagnostic strategies will not impact on the incidence of the disease or the chance of getting breast cancer, but aims to improve survival by downstaging. The impact of any or all of these measures on survival is diffi cult to estimate or model.…”
Section: Early Diagnosismentioning
confidence: 99%
“…MRI is a highly sensitive imaging technique, but lacks information on specificity, and thus it has high rate of false positive results [7]. The impact of misdiagnosis on the patient is considerable, particularly when they are confronted with unnecessary surgeries.…”
Section: Introductionmentioning
confidence: 99%